EzSports Enterprise / Mohamad Aidil Arif Adnan - Adnan, Mohamad Aidil Arif (2020)
EzSports Enterprise is a company that selling goods sporting equipment. The Agility Ladder is a product made for those individuals engaged in sporting activities. Our main objective is to succour people who loves to exercise and importantly, to achieve the performance to the standard expected by the customers and also exceed customer satisfaction. The target market for this product is for athletes. The Eztech agility ladder can compete with another company because the product has a sensor to count the step that the user made. The product idea is to allow athletes, coaches, and outdoor recreation people to recognise the issue during training. This product helps by using the sensor to count the move the consumer is making. We are providing sports equipment at lowest price. Correspondingly, EzSports Enterprise is here to provide people with great sporting gear. Our main target is to promote our sporting equipment and gain more profits by providing good and excellent product to customers that will eventually help to increase gross domestic product to the country, and to become a very well-known company all by people across the place later in becoming a successful in upcoming years. The business is based on partnership where it consists of five members which hold important positions in the company such as General Manager, Administration Manager, Operational Manager, Marketing Manager and Financial Manager. Every person has their own role and responsibilities towards the organization.